Monitoring the Inorganic and Organic Acids in the Atmosphere of the Urban Area of the City of Salvador, Brazil - Lícia P. S. Cruz; Elisvan R. Mota; Vânia P. Campos; Franciele O. Santana; Sâmeque R. Luz; Daniela F. Santos (International Research in Environment, Geography and Earth Science Vol. 8, 2021)
Air pollution has been considered the main environmental degradation agent of the planet. The major air pollution problems arise from the release of gases and particles into the atmosphere, and the main sources are vehicles and industrial activities. Different fuels are used in Brazil and there is little knowledge about the presence of organic and inorganic acids in the atmosphere of the Brazilian cities. HNO3, HCl, HCOOH and CH3COOH were sampled in the gas phase using passive samplers and thermodiffusion system, in which the H2SO4 particulate was also sampled, in five sites of Salvador. Ion chromatography analyses showed that the organic and inorganic acids measured contributed on average with 89% and 11%, respectively, to the acidity of the city’s atmosphere. The strong correlations between HCOOH, CH3COOH and HCl with CO and NO2 indicated a common source for these compounds, predominantly from vehicular emissions. H2SO4 showed strong correlations with PM10 and with its precursor SO2; and HNO3 with NO2 and NO precursors. Most of the compounds presented negative correlations with meteorological parameters. PCA and HCA confirmed these observations. The ratios [HCOOH]/[CH3COOH] varied from 0.69 – 1.9, typical of urban areas. Pearson’s correlation analysis showed that all acids determined in this study were influenced by vehicle emissions. Important correlations were established among the studied acids, meteorological parameters and criteria air pollutants in the atmosphere of this city through PCA and HCA.